PENGEMBANGAN LEMBAR KEGIATAN SISWA BERBASIS STRATEGI METAKOGNITIF PADA MATERI PEWARISAN SIFAT - KARYA N, FRIDA (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
Inheritance contains some highly difficult concepts because it seems complex and complicated. In addition, it needs a long time and suitable equipments to do practical work. So that it requires worksheets to overcome the problems and can help student to understand about inheritance. One ofÂ ways that can be done is developing student worksheets based on metacognitive strategy. The student worksheets are expected to encourage students to understand with their own ability. This research aims to determine the feasibility of the student worksheets, studentâ€™s metacomprehension skills, studentâ€™s learning outcomes, studentâ€™s response to the student worksheets and to obtain studentâ€™s worksheets that are feasible. This research used 4-D model. In this case, the research only applied three steps (3-D models). They are â€œdefineâ€, â€œdesignâ€, and â€œdevelopâ€. The research subject are student worksheets based on metacognitive strategy on inheritance. The student worksheets were tried out in class IX of Jenangan Junior High School 2 with 20 students, using â€œone shot case studyâ€ method. The results show that the student worksheets developed were feasible with 3,67 average of score (very good category). The average studentâ€™s metacomprehension skills were categorized very good. The studentâ€™s learning outcomes showed that 85% of students were mastery with 60% of learning objectives are mastery and the students responded positively to the student worksheets. Â Keyword: student worksheets based on metacognitive strategy, inheritance, 4-D models Â